Analysis of the Relationship between the Exchange Rate and the Oil Price in the Iraqi Economy after 2003 (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Crude oil prices are one of the most volatile economic variables in the world economy, especially oil countries. These fluctuations often coincide with fluctuations in the dollar exchange rate. These fluctuations in the exchange rate of the US dollar, whether up or down, and these fluctuations in crude oil prices for oil-exporting countries lead to an improvement in the value of their currencies against the currencies of other countries, The impact of oil prices to the exchange rate may be indirectly through other factors associated with oil prices trading Kalmizan and current account and international reserves, and these factors in turn lead to a change in the exchange rate and the study aims to reveal the correlation between the price of crude oil exchange rate in Iraq. The research is based on the hypothesis that there is a relationship between the foreign exchange rate and the price of oil in the Iraqi economy after 2004, and the problem of research is the impact of fluctuations in oil prices on most of the exporting countries, and the countries where the main source in achieving financial resources, including Iraq, as oil represents These countries seek to diversify their financial and economic sources in order to reduce dependence on oil and avoid the risks of low crude oil prices on their economies, including their impact on the price of oil. As a result of the study, Iraq's dependence on oil revenues mainly in supplying the public budget, which makes it vulnerable to crises in the case of low prices, especially as Iraq lacks diversification of public revenues and do not use those revenues in the development of other economic sectors and high degree of reliability of oil-exporting countries. On oil production and exportation, especially the Arab countries in financing their spending and economy, any fluctuation in the price of oil can cause instability of their economies, leaving them vulnerable to worsening budget problems and their effects of large-scale damage and the exchange rate.